Cloacal Exstrophy with Normal Penis and Urethra - A Rare Variant - Ruchira Nandan; Bhanumurthy Kaushik Marripati; Ajit Kumar Vidhyarthy; Vaibhav Pandey (Wolters Kluwer Medknow Publications, 2024)
Classically, cloacal exstrophy presents with omphalocele, bladder exstrophy, imperforate anus, and spinal defects. We report a rare variant of cloacal exstrophy in a 6-day-old male with an intact lower abdominal wall, normal penis, and urethra. Only two such cases have been reported in the literature.